Rare bird documentation form for Northern Goshawk west of Corydon, 1982 - Moore, Francis L.et al (1982)
Rare bird documentation form for a Northern Goshawk at the Wendell Tuttle Farm west of Corydon in Wayne County, IA on November 27, 1982. Epson - sheet feed